2019
DOI: 10.1002/slct.201902246
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Self‐Assembled Preparation of Porous ZnFe2O4/MIL‐100(Fe) Nanocomposites and Their Visible‐Light Derived Photocatalytic Properties

Abstract: Herein, a facile self‐assembly synthesis of magnetic porous ZnFe2O4/MIL‐100(Fe) composites by slowly oxidizing Fe2+ to Fe3+ was reported. By this method, ZnFe2O4/MIL‐100(Fe) composites with a particle size of about 300 nm can be obtained at room temperature and pressure. The efficacy of the products was evaluated for the degradation of Rhodamine B (RhB) under visible light irradiation. It was found that the introduction of MIL‐100(Fe) can not only significantly improve the adsorption capacity of composites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…By contrast, metalorganic frameworks (MOFs) provide excellent support, having the features of stability, adjustable tunnels, ultra-high specific surface area, and high catalytic efficiency (Kang et al, 2019;Li D. D. et al, 2019). Examples are PTA@MIL-53 (Fe) (Nikseresht et al, 2017), AILs/HPW/UiO-66-2COOH (Xie and Wan, 2019b), and ZnFe 2 O 4 /MIL-100(Fe) (Hu et al, 2019). Meanwhile, our previous studies showed the esterification of oleic acid or lauric acid with methanol over silicotungstic acid and nickel salts of Keggin-type heteropolyacids encapsulated into metal-organic framework (UiO-66) hybrid nanocatalysts that had excellent activity and reusability (Zhang et al, 2019b(Zhang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, metalorganic frameworks (MOFs) provide excellent support, having the features of stability, adjustable tunnels, ultra-high specific surface area, and high catalytic efficiency (Kang et al, 2019;Li D. D. et al, 2019). Examples are PTA@MIL-53 (Fe) (Nikseresht et al, 2017), AILs/HPW/UiO-66-2COOH (Xie and Wan, 2019b), and ZnFe 2 O 4 /MIL-100(Fe) (Hu et al, 2019). Meanwhile, our previous studies showed the esterification of oleic acid or lauric acid with methanol over silicotungstic acid and nickel salts of Keggin-type heteropolyacids encapsulated into metal-organic framework (UiO-66) hybrid nanocatalysts that had excellent activity and reusability (Zhang et al, 2019b(Zhang et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…7b), the peaks at 284.7 eV and 288.5 eV, which can be assigned to C-C/C]C of phenyl and C]O of carboxyl, respectively. 39 Moreover, four peaks are observed at 855.6 eV, 861.5 eV are conrmed to Ni 2p 3/2 and 873.5, 879.7 eV are ascribed to Ni 2p 1/2 , indicating the valence state of Ni is +2 (Fig. 7c).…”
Section: Catalyst Characterizationmentioning
confidence: 94%
“…Among preparation methods, the hydrothermal method is the preferred choice because of its simplicity, ease of implementation, and high efficiency. [26][27][28][29][30][31] In the environmental eld, MIL-100(Fe) is also capable of removing many pollutants, such as heavy metals (Cr 6+ ), 29,31 RhB, 32,33 tetracycline antibiotic, 31 and microcystin-LR. 34 Although both Mn 2 O 3 and MIL-100(Fe) can be used as photocatalysts under visible light due to their low bandgaps (i.e., 1.44 eV and 2.6-2.7 eV, respectively), the high recombination of photoexcited electrons and holes in these two individual materials hinders their practical application for photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…These photoexcited electron-hole pairs are easily recombined together with a very short lifetime unless they are separated and consumed. In the M100Mn material, the electromagnetic eld at the interface of Mn 2 O 3 and MIL-100(Fe) helps to move the electrons and holes in opposite ways 56. Specically, the electrons from the conduction band of Mn 2 O 3 transfer to the conduction band of MIL-100(Fe) with higher potential.…”
mentioning
confidence: 99%